Effects of Different Microbial Fertilizer Applications on Yield and Yield Components in Cowpea (Vigna unguiculata L.) Varieties - Hamdi Özaktan; Hüseyin Atalay; Melike İncetekin; Oğuz Erol (Turkish Journal of Agriculture: Food Science and Technology, 2025)
This study was conducted to investigate the effect of different foliar microbial fertilizer applications on yield and yield components of some cowpea (Vigna unguiculata L. Walp) cultivars (Akkız-86 and Karagöz-86). The research was conducted in 2022 growing season under Kayseri ecological conditions. When the results of the study were evaluated, average values of plant height varied between 80.294-84.668 cm, number of main branches per plant varied between 1.749-1.919 pieces/plant, first pod height varied between 44.326-50.012 cm, number of pods varied between 8.449-11.056 pieces/plant, number of seeds per pod varied between 4.925-5.591 pieces/plant; the highest value in unit area grain yield was obtained from Imed microbial fertilizer with 232.814 kg/da. It can be said that microbial fertilizers positively affect grain yield in cowpea plants.